Rare complications of chicken pox in immunocompetent children: Acute respiratory distress syndrome. (January 2022) - Mahto, Subodh Kumar; Gupta, Kritika; Pasricha, Nitasha; Agarwal, Nagina; Sheoran, Ankita
Chickenpox is a highly contagious disease caused by varicella zoster virus. Fever and papulovesicular rash are hallmarks of this disease. These manifestations are self-liming and complete recovery is seen in most cases. We report two cases of chickenpox infection where the rare and atypical manifestations of acute respiratory distress syndrome with pleural effusion were seen.